THE IMPACT OF CONTRACT LEARNING STRATEGY ON DEVELOPING MATHEMATICAL THINKING SKILLS IN MATHEMATICS SUBJECT FOR MIDDLE SCHOOL STUDENTS - Heba Thamer Ahmed (Scholars Digest Publishing, 2024)
This research aims to understand the impact of using the contract learning strategy on developing mathematical thinking skills among middle school students. The research provides an overview of the contract learning strategy and how to apply it in the context of teaching mathematics. The research emphasizes the importance of developing mathematical thinking skills among middle school students, as these skills are essential for achieving deep understanding and solving problems effectively in mathematics and in general life. The research presents the contract learning strategy as an effective tool to achieve this goal, as it encourages students to actively participate in the learning process and develop their mental and strategic skills. The research discusses previous studies and practical experiments showing the impact of the contract learning strategy on improving students' mathematical thinking skills, including critical thinking ability, problem analysis, mathematical reasoning, and deeper understanding of mathematical concepts. The research concludes with guidelines for teachers on how to implement the contract learning strategy in teaching mathematics to middle school students, emphasizing the importance of providing an educational environment that encourages critical thinking and collaboration among students in solving mathematical problems.
Keywords: Impact, Contract Learning Strategy, Mathematical Thinking Skills, Mathematics, Middle School Students.